The mediating role of early maladaptive schemas on the relationship between illness perception and pain coping strategies among adolescents diagnosed with migraine - Kayar, Ozan; Altinoğlu Dikmeer, İlkiz and Güler Aksu, Gülen and Toros, Fevziye and Özge, Aynur (Frontiers in Neurology, 2023)
Objective This study aimed to examine the mediating role of early maladaptive schemas on the relationship between illness-related perceptions and pain coping strategies among adolescents diagnosed with migraine. Material and methods A total of 134 adolescents (aged 12–18 years) diagnosed with migraine with and without aura participated in the study. The Illness Perception Questionnaire, the Pain Coping Questionnaire, and the Early Maladaptive Schema Questionnaires Set for Children and Adolescents were used. Results The intensity of using desperate ways of coping with pain was higher among adolescents who perceive migraine as a chronic disease (β = 0.199, p < 0.05) even if they have episodic attacks and who have higher levels of coherency in understanding the illness (β = 0.256, p < 0.01). First, full mediations of over-vigilance/inhibition and impaired autonomy/performance schema domains on these relations were observed. Second, the increases in negative cognitive (β = 0.199, p < 0.05) and emotional (β = 0.280, p < 0.01) representations related to the consequences of the illness lead to an increase in the uncontrolled and frequent use of analgesic drugs where the partial mediating role of over-vigilance/inhibition schema domain on this correlation is observed. The perceptions about the negative as well as serious consequences of migraine are related to both the self-active behaviors (β = 0.181, p < 0.05) and the conscious cognitive attempts (β = 0.207, p < 0.05) as effective coping strategies, which is an unexpected finding. The disconnection/rejection schema domain had a full mediation role on both relations. Conclusion The results suggest that early maladaptive schemas are essential factors that affect the migraine coping processes of adolescents.